Comparison of the clinical and laboratory characteristics of neuromyelitis optica spectrum disorder with or without cerebrospinal fluid oligoclonal bands: a cohort with 36-month follow-up - Yang, Wenbo; Liu, Xiaoni; Wei, Jie; Yu, Hai; Wu, Wanqing; Wang, Jingguo; Deng, Bo; Wu, Xiaoqin; Chen, Xiangjun; Zhang, Xiang (Frontiers in Immunology, 2025)
PurposeThis study aimed to explore the significance of cerebrospinal fluid (CSF) oligoclonal bands (OCBs) in the clinical diagnosis and evaluation of neuromyelitis optica spectrum disorder (NMOSD).MethodsThe demographic and clinical data of 143 aquaporin-4 immunoglobulin G (AQP4-IgG)-positive NMOSD patients were collected and analyzed, including the gender, age, clinical symptoms and signs, status of CSF OCBs, location and length of the affected spinal cord vertebral segments, Expanded Disability Status Scale (EDSS) at the first attack and at 36-month follow-up, relapse times within 36 months, concomitant connective tissue disease (CTD), and status of other autoimmune antibodies (oAIA).ResultsThere were 15 patients (10.5%) who were positive for OCBs (OCBs+). In contrast to those with negative OCBs (OCBs−), more OCBs+ cases had concomitant CTD [5/15 (33.3%) vs. 11/128 (8.6%), p = 0.014] and oAIA [9/15 (60.0%) vs. 37/128 (28.9%), p = 0.020]. OCBs+ patients had higher CSF cell counts [15.0 (27.0)/mm3vs. 5.0 (12.0)/mm3, p = 0.008], higher IgG index [0.68 (0.23) vs. 0.52 (0.15), p < 0.001], and more relapses within 36 months [2.0 (3.0) vs. 1.0 (2.0), p = 0.039] than OCBs− patients. More OCBs+ patients had polynuclear cell predominance in the CSF than OCBs− patients (p = 0.032). There were no significant differences between the OCBs+ and the OCBs− patients in the distribution of lesion locations; the length of the affected spinal cord vertebral segments; the concentration of CSF protein and the albumin quotient; the EDSS score at the time of lumbar puncture and at 36-month follow-up, and the onset episode, the relapse, and cumulative clinical syndrome profiles (all p > 0.05).ConclusionsFor AQP4-IgG-positive NMOSD patients, positivity for CSF OCBs is associated with higher CSF cell counts and a higher likelihood to have concomitant CTD and oAIA. OCBs+ is not uncommon in NMOSD and may predict more frequent relapses, but not a more serious illness.